Anaerobic digestion process deactivates major pathogens in biowaste: A meta-analysis. (January 2022) - Ma, Guiling; Chen, Yanting; Ndegwa, Pius
Abstract: Foodborne illnesses associated with biowaste use are a threat to human health unless integral pathogens are inactivated prior to biowaste utilization for crop production or prior to release to the environment. Anaerobic digestion (AD) is mainly known for extraction of renewable bio-methane from such biowaste. Although past studies indicate some benefits, with respect to pathogen inactivation, the results on the process efficacy, are inconsistent. The goal of this study was to amalgamate available data and critically analyze it, via meta-analyses, to determine AD efficacy on pathogen inactivation under normal operating conditions. Web of Science and other related databases running up to December 9, 2020, were mined for relevant data. A total of 102 studies were found suitable for our meta-analysis. Results indicated that ambient digestions did not have significant effects on fecal coliforms inactivation (ambient batch: SMD -3.2; 95% CI -6.9 0.6; I 2 98.3%; P = 0.09; ambient continuous: SMD -10.8; 95% CI -30.8 9.1; I 2 99.8%; P = 0.27). Fecal coliforms in the effluent were above 3 or even above 6.3 log10 (MPN g −1 [TS]), and E. coli in some effluents were above the safety threshold (i.e., > 4 log10 (MPN g −1 [TS]) (significant decrease through mesophilic AD (ambient batch: SMD -3.2; 95% CI -6.2 -0.1; I 2 97.3%; P = 0.04; ambient continuous: SMD -22.8; 95% CI -24.3 -21.3; I 2 0.0%; P < 0.01)). Mesophilic digestion mainly resulted in Class B effluent ( fecal coliforms < 6.3 log10 (MPN g −1 [TS]) (mesophilic batch: SMD -12.7; 95% CI -16.5 -9.0; I 2 97.1%; P < 0.01; mesophilic continuous: SMD -7.8; 95% CI -12.4 -3.2; I 2 86.3%; P < 0.01); E. coli < 4 log10 (MPN g −1 [TS]) (mesophilic batch: SMD -12.3; 95% CI -16.2 -8.4; I 2 97.4%; P < 0.01; mesophilic continuous: SMD -10.5; 95% CI -15.1 -6.0; I 2 69.2%; P < 0.01)). Thermophilic digestion, however, mainly produced Class A effluent ( fecal coliforms < 3 log10 (MPN g −1 [TS]), (thermophilic continuous: SMD -29.5; 95% CI -44.0 -15.0; I 2 97.4%; P < 0.01) and E. coli < 4 log10 (MPN g −1 [TS]), (thermophilic batch: SMD -31.2; 95% CI -34.7 -27.7; I 2 11.0%; P < 0.01; thermophlic continuous: SMD -18.0; 95% CI -20.1 -15.9; I 2 61.2%; P < 0.01)), which was significant in pathogen inactivation. In ambient digestions, AD effluent had < 5 log10 salmonella reduction and did not meet safety threshold. In mesophilic and thermophilic digestions, AD effluent mainly had > 5 log10 salmonella reduction. Several treatments (acid, alkaline, heat, and ozonation) prior to AD processes were found to promote pathogen inactivation (Class A or Class B biosafety level), especially in ambient conditions ( fecal coliforms in ambient batch: SMD -6.5; 95% CI -8.9 -4.1; I 2 87.4%; P = 0.004), which improved pathogen inactivation to below the bio-safety level. Process intermediate substrates (VFA and ammonia) were also positive at improving pathogen inactivation (VFA of 4170 mg L −1 in ambient batch digester improved digestate fecal coliform to biowaste Class A level). Methane yield was found to be a potential indicator for E. coli inactivation in the AD process. Overall, AD under ambient regime was not successful in pathogen inactivation without pre-treatment. Mesophilic and thermophilic digestions were mainly successful in pathogen inactivation even without pre-treatment. Anaerobic digestion, therefore, provides an excellent opportunity to mitigate biowaste biosafety, and decrease human expose to foodborne related pathogens. Graphical abstract: Image 1 Highlights: Ambient-temperature AD does not have significant effect on fecal coliform inactivation. Ambient-temperature AD have only limited effect on E.coli and salmonella inactivation. Mesophilic or thermophilic AD mainly produce effluent meeting pathogens biosafety threshold. Biowaste pretreatments significantly enhanced pathogen inactivation in ambient and mesophilic regimes. Process intermediate products (VFA and ammonia) improved pathogen inactivation.